1991
DOI: 10.1128/aac.35.7.1479
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose and three-day regimens of ofloxacin versus trimethoprim-sulfamethoxazole for acute cystitis in women

Abstract: We compared the safety and efficacy of a single 400-mg dose of ofloxacin, ofloxacin (200 mg) once daily for 3 days, and trimethoprim-sulfamethoxazole (160:800 mg) twice daily for 7 days for the treatment of acute uncomplicated cystitis (urinary tract infection [UTI]) in women. At 5 weeks posttreatment, 35 (81%) of 43 patients treated with single-dose ofloxacin, 40 (89%) of 45 treated with 3 days of ofloxacin, and 41 (98%) of 42 treated with trimethoprim-sulfamethoxazole were cured (P = 0.03, single-dose oflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 19 publications
7
29
1
Order By: Relevance
“…Furthermore, when the effects of treatment were evaluated 5 to 9 days after therapy, both drugs provided marked improvement or relief from the signs and symptoms of UTI in more than 92% of all patients treated, including those who were not evaluable because of low urine colony counts (Ͻ10 5 CFU/ml) at study entry (2). The clinical and bacteriologic outcome rates in the ofloxacin arm of this study are similar to those reported previously for the drug used for this indication (5,24). Clinical findings and bacteriologic results in this study were in agreement for all but a few patients; one in each group was deemed a success clinically but had a bacteriologic response of failure, while three in the sparfloxacin group and seven in the ofloxacin group had positive bacteriologic responses but were designated clinical failures.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, when the effects of treatment were evaluated 5 to 9 days after therapy, both drugs provided marked improvement or relief from the signs and symptoms of UTI in more than 92% of all patients treated, including those who were not evaluable because of low urine colony counts (Ͻ10 5 CFU/ml) at study entry (2). The clinical and bacteriologic outcome rates in the ofloxacin arm of this study are similar to those reported previously for the drug used for this indication (5,24). Clinical findings and bacteriologic results in this study were in agreement for all but a few patients; one in each group was deemed a success clinically but had a bacteriologic response of failure, while three in the sparfloxacin group and seven in the ofloxacin group had positive bacteriologic responses but were designated clinical failures.…”
Section: Discussionsupporting
confidence: 79%
“…There was a relatively high level of adverse events reported in both arms of the study (43.2% of patients overall), but this level was not atypical given the active method used for elicitation (5,20). The incidence of adverse events possibly or probably related to study drug, 27.9%, was also high, but again, it was not atypical for a conservative causative analysis (9).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For trimethoprim-sulfamethoxazole, single-dose therapy is likely optimal (4,12,15). For other antimicrobial agents effective as short courses of therapy, 3 days of therapy has been suggested to be appropriate (6,8,9,16). For the fluoroquinolone antimicrobial agents, in particular, 3 days of therapy seems necessary because of the high failure rates of single-dose therapy of infection with Staphylococcus saprophyticus, the second most frequent infecting organism in this syndrome (5,8,17).…”
mentioning
confidence: 99%
“…3). The efficacy of ofloxacin is greater than TMP-SMX with recurrence rates of 8% to 9% 6 weeks after therapy has been completed (Hooton et al 1991). Other fluoroqinolones have similar efficacy however they should be regarded as a second line treatment option due to their high cost and to preserve their sensitivity against uropathogens.…”
Section: Managementmentioning
confidence: 96%